Comparing Facebook Users and Facebook Non-Users: Relationship between Personality Traits and Mental Health Variables - An Exploratory Study. - Julia Brailovskaia; Jürgen Margraf (PLoS ONE, 2016)
Over one billion people use Facebook as a platform for social interaction and self-presentation making it one of the most popular online sites. The aim of the present study was to investigate differences in various personality traits and mental health variables between Facebook users and people who do not use this platform. The data of 945 participants (790 Facebook users, 155 Facebook non-users) were collected. Results indicate that Facebook users score significantly higher on narcissism, self-esteem and extraversion than Facebook non-users. Furthermore, they have significantly higher values of social support, life satisfaction and subjective happiness. Facebook non-users have (marginally) significantly higher values of depression symptoms than Facebook users. In both groups, extraversion, self-esteem, happiness, life satisfaction, resilience and social support, on the one hand, and depression, anxiety and stress symptoms, on the other hand, are negatively correlated. Neuroticism is positively associated with depression, anxiety and stress symptoms. However, significant differences exist between Facebook users and Facebook non-users regarding some associations of personality traits and mental health variables. Compared to Facebook non-users, the present results indicate that Facebook users have higher values of certain personality traits and positive variables protecting mental health. These findings are of particular interest considering the high importance of social online-platforms in the daily life of many people.